2006
DOI: 10.1007/s11249-006-9176-7
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviors of surfactant-functionalized carbon nanotubes as lubricant additive in water

Abstract: The multi-walled carbon nanotubes (MWCNTs) are functionalized by self-assembled surfactant layers after sonication in anionic surfactant sodium dodecyl sulfate (SDS) aqueous solution. The tribological properties of the SDS-functionalized MWCNTs as additive in water-based lubricants were evaluated with a four-ball tester. The results show that the SDSfunctionalized MWCNTs exhibit good anti-wear and friction reduction properties as well as enhanced load-carrying capacity. The maximum non-seizure load (PB value) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(78 citation statements)
references
References 11 publications
(12 reference statements)
2
72
0
Order By: Relevance
“…Based on TEM-EELS analysis of the rubbed surfaces they suggested that the carbon particles may stabilise maghemite, a low friction form of iron oxide. Carbon nanotubes have also been investigated as potential boundary lubricant additives and found to reduce significantly both friction and wear [223,224]. In the last few years there has been considerable focus on graphene as a potential lubricant, including its use as an additive dispersed in oil.…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on TEM-EELS analysis of the rubbed surfaces they suggested that the carbon particles may stabilise maghemite, a low friction form of iron oxide. Carbon nanotubes have also been investigated as potential boundary lubricant additives and found to reduce significantly both friction and wear [223,224]. In the last few years there has been considerable focus on graphene as a potential lubricant, including its use as an additive dispersed in oil.…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 99%
“…The inorganic fullerenes have a layer lattice structure which, once exfoliation occurs, is believed to provide low shear strength sheets that adhere to the surfaces to reduce sliding friction in a similar fashion. Other nanoparticulate solids also having layer lattice structure, such as hexagonal boron nitride [224,235] and boric acid [236], have also been shown to reduce friction, probably by a similar mechanism.…”
Section: Nanoparticle Additive Research; 1990 To Presentmentioning
confidence: 99%
“…In addition to that, their shape, high aspect ratio and high flexibility rendered them as a promising candidate for solid lubrication or as a lubricant additive in tribological applications. Several studies have proved the ability of CNTs to reduce friction and wear; for example, when used as the reinforcement phase in composites [3][4][5][6][7][8][9], as a protective film [10][11][12][13], solid lubricant [8][9][10]12,14,15], or lubricant additive [16][17][18][19]. Although all of these systems show improvements to a different extent, the tribo-mechanisms inducing these effects are clearly differing and not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In order to further improve the tribological performance of the composite coatings in a space environment, Wang's group has used carbon nanomaterials (graphene and carbon nanotube) as ionic liquid lubricant additives due to their high mechanical strength, high thermal conductivity and excellent thermal stability, which make them more suitable candidates than traditional additives. Graphene-and CNTs-based additives for base oil have already been studied in detail [90][91][92][93], with the results indicating that they could significantly improve the lubricant's tribological properties and lifetime as they are heat resistant, durable and self-lubricating. Wang's group firstly fabricated composite lubricating systems composed of IL with graphene and CNTs as lubricant additives and DLC films (DLC/IL/graphene and DLC/IL/graphene+CNTs), and evaluated their potential for space tribology.…”
Section: Carbon-based Solid-liquid Synergetic Lubricating Materialsmentioning
confidence: 99%